DEVELOPMENT OF ELECTRONIC MODULES FOR DERIVATIVES OF ALGEBRAIC FUNCTIONS TO FACILITATE MATHEMATICAL COMPREHENSION ABILITY OF CLASS XI SENIOR HIGH SCHOOL STUDENTS - Dwi Orista; Armis (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2023)
This study aims to produce an electronic module for derivatives of algebraic functions to facilitate the mathematical comprehension ability of class XI senior high school students who have met the requirements for validity and practicality. The development model used is the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The sample in this assessment is class XII MAN 2 students in Pekanbaru City. Two data collection instruments for the electronic module development are a validation sheet to see the electronic module's validity level and a student response questionnaire to see the electronic module's practicality level. Based on the validation results from three experts, it was obtained that the electronic module has an average score of 3.47 with a very valid category. The trials conducted on students were carried out twice, namely small group trials and then large group trials. Based on the results of a small group trial of students, it was obtained that the electronic module had an average score of 3.67 with a very practical category. Based on the results of a large group trial of students, it was obtained that the electronic module had a score of 3.78 with a very practical category. Therefore, it is concluded that the electronic module of derived material of algebraic functions developed has met the requirements of validity and practicality to facilitate the mathematical comprehension ability of class XI SMA / MA students.